Implementasi Metode Kisah dalam Pembelajaran Akidah Akhlak di Madrasah Aliyah - M Irfangi (Jurnal Kependidikan, 2017)
Learning is influenced by several components, such as educators, learners, learning materials, learning methods, infrastructure and the environment. Learning method has a very important role for the achievement of goals, because without methods, the subject matter can not be delivered effectively. Among the methods that are effective in education on the subjects of Akidah Akhlak is the story method. The technique used in this method is to reveal historical events originating from the Qur'an containing moral, spiritual, and social values, both on stories of goodness and injustice. This is a qualitative research and the main data is related to Akidah Akhlak Learning of in MAN 2 Banyumas. The data were obtained through observation, interview and documentation. The application of story method in akidah akhlak learning in MAN 2 Banyumas represents a variation in the learning process and is expected to help educators in delivering the subject matter. through this method,students will be moremore enthusiastic and more easily understand the material during the learning process.